1995
DOI: 10.1111/j.1600-0714.1995.tb01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased lysyl oxidase activity in fibroblasts cultured from oral submucous fibrosis associated with betel nut chewing in Taiwan

Abstract: Growth characteristics and lysyl oxidase activity of fibroblasts derived from human normal mucosa (NM) and oral submucous fibrosis (OSF) associated with betel nut chewing were compared in cell cultures. The growth rates of cultured cells were identified by plating 5 x 10(5) cells/35 mm culture dish (Day 0) and every 24 hours cell proliferation was determined by quantifying the cell number (using a hemocytometer). The third to seventh passages were used. A medium without serum but supplemented with 5 mg/ml bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 24 publications
(4 reference statements)
2
44
0
Order By: Relevance
“…This is a copper dependent enzyme [19] and plays a key role in collagen synthesis. The possible role of copper as a mediator of fibrosis is supported by the demonstration of up regulation of this enzyme in OSF biopsies [30] and in OSF fibroblasts compared to normal fibroblasts grown in culture [21]. We also found a similar effect in our case and the effect was more prominent when these cells were exposed to arecoline 10 lM, 24 h. b-aminopropionitril (BAPN, 100 lM), an irreversible LOX inhibitor, was found to complete reversal of LOX activity as measured by ELISA and western blot analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a copper dependent enzyme [19] and plays a key role in collagen synthesis. The possible role of copper as a mediator of fibrosis is supported by the demonstration of up regulation of this enzyme in OSF biopsies [30] and in OSF fibroblasts compared to normal fibroblasts grown in culture [21]. We also found a similar effect in our case and the effect was more prominent when these cells were exposed to arecoline 10 lM, 24 h. b-aminopropionitril (BAPN, 100 lM), an irreversible LOX inhibitor, was found to complete reversal of LOX activity as measured by ELISA and western blot analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence implicates collagen-related genes in the susceptibility and pathogenesis of OSF [9]. The activity of lysyl oxidase (LYOXase), an extracellular enzyme which stabilizes the collagen and prevents degradation of collagenase in oral mucosa, was found to increase in fibroblasts cultured from OSF patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…These atrophic epithelial or cancer tissues might contain less amount of NADH and thus had a lower 460-nm emission peak than the corresponding lesions in non-OSF patients. In Taiwan, oral premalignant and malignant lesions are commonly found in OSF patients and AQ-chewing habit prevails in patients with oral premalignant and malignant lesions [22]. As AQ-chewing habit may cause obscure to different degrees of fibrosis in the oral mucosa, autofluorescence spectra measured from premalignant, malignant and their surrounding normal tissues in AQ-chewers or OSF patients may be distorted due to the presence of underlying tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…6,14,15 The increase in copper may also be attributed to the increased production of copper containing ceruloplasmin by liver as an anti-inflammatory response or due to decrease in catabolism of serum ceruloplasmin. 16 In our study, the mean serum zinc level among 30 OSMF patients was found to be lower than the controls.…”
Section: Discussionmentioning
confidence: 99%